2013
DOI: 10.1179/1743284713y.0000000257
|View full text |Cite
|
Sign up to set email alerts
|

Formation of ultrafine structure in as cast Ti7CuXSn alloys

Abstract: The purpose of the present study was to investigate the microstructure and microhardness of novel Ti7CuXSn alloys. Ti7CuXSn alloys with x = 0, 1, 2·5 and 5 wt- were synthesised using a well developed arc melting and casting method. The microstructure was analysed by means of optical microscopy, SEM and X-ray diffraction methods. The cellular grain size dG, lamellar spacing λL, volume fraction of Ti2Cu phases fv and microhardness HV were measured. The addition of Sn content into the Ti7Cu alloy can effectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 30 publications
3
17
0
Order By: Relevance
“…It is noteworthy that adding 5 wt.% Sn content refined the microstructure greatly, increased the volume fraction of Ti 2 Cu phase (mark d), and gradually eliminated the basket-weave structure. A similar result was also reported by Tsao et al [16]. The initial E OCP for the Ti 7 Cu sample was approximately − 232.6 mV Ag/AgCl , and it rapidly increased and near stabilized in the region of − 176.3 mV Ag/AgCl after 60 min.…”
Section: Microstructuressupporting
confidence: 85%
See 2 more Smart Citations
“…It is noteworthy that adding 5 wt.% Sn content refined the microstructure greatly, increased the volume fraction of Ti 2 Cu phase (mark d), and gradually eliminated the basket-weave structure. A similar result was also reported by Tsao et al [16]. The initial E OCP for the Ti 7 Cu sample was approximately − 232.6 mV Ag/AgCl , and it rapidly increased and near stabilized in the region of − 176.3 mV Ag/AgCl after 60 min.…”
Section: Microstructuressupporting
confidence: 85%
“…Recently, Tsao et al [16] reported that adding Sn into the Ti 7 Cu alloy can effectively induce the transformation of an ultrafine α′ martensite microstructure and increase the volume fraction of the Ti 2 Cu phase. Tin (Sn) is a non-toxic, non-allergenic alloying element [17] used to strengthen Ti alloys [1].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the release of Al and V ions from the alloy might cause cause serious problems 7,8 . Therefore, many efforts have been working out to develop non-toxic elements Ti alloys, such as Ti-Cu 9,10 , Ti-Sn 11 , Ti-Cu-Sn 12,13 , Ti-Nb 14,15 and Ti-15Zr-Mo alloys 16 . It is well known that alloying elements alter the transformation temperatures, phases/crystal structure of titanium alloys 4,5,17 .…”
Section: Introductionmentioning
confidence: 99%
“…This limited grain size significantly increases the alloy strength 27 . Tsao et al 12 established that the addition of Sn to Ti7CuXSn (X = 0 -5 wt. %) alloys can effectively increase the solubility of Cu in the eutectoid microstructure (α-Ti + Ti 2 Cu), induce the transformation of an ultrafine α′ martensite microstructure and increase the volume fraction of the Ti 2 Cu phase.…”
Section: Introductionmentioning
confidence: 99%